Analysis of Employee Organizational Commitment: Using Four Independent Variables - Budiono, Aris; Tarigan, Hairani; Khalid, Jamaludin (Universitas Djuanda, 2024)
This research focuses on exploring effective efficiency in employee treatment by examining organizational commitment influenced by organizational culture and compensation, with performance and satisfaction serving as mediators. The research location was conducted at an accommodation service in Lampung with a population of 80 employees. Data collection used a saturated sampling technique for 77 employees who wanted to contribute to filling in statements related to this research. SEM-PLS is employed to uncover direct and indirect effects, yielding the following findings: Performance is directly impacted by organizational culture and compensation. Organizational commitment, however, is not directly affected by either organizational culture or compensation. On the other hand, job satisfaction is directly influenced by organizational culture and compensation. Furthermore, organizational commitment is directly influenced by performance rather than job satisfaction. Regarding indirect influence, performance variables and job satisfaction have no significant effect, so the two exogenous variables, namely organizational culture and compensation, can directly influence organizational commitment without going through performance or job satisfaction variables